Thermal stability and Kinetic Study of rigid and plasticized Poly(vinyl chloride)/Poly(methylmethacrylate) blends. Issue 2 (26th June 2014) - Aouachria, K.; Massardier‐Nageote, V.; Belhaneche‐Bensemra, N.
Abstract : The thermal stability and kinetic parameters for degradation of rigid and plasticized poly(vinyl chloride)/poly (methylmethacrylate) blends have been investigated by using nonisothermal thermogravimetry in a flowing atmosphere of air. For that purpose, blends of variable composition from 0 to 100 wt% were prepared in the presence (15, 30, and 50 wt%) and in the absence of di‐(‐2‐ethyl hexyl) phthalate as plasticizer. Measurements were carried out in the temperature range of 30–550°C and at various heating rates (5, 10, 20, and 40°C/min). The kinetic parameters ( E a and A ) were determined by applying the integral Kissinger method. Results indicate that these parameters and the thermal stability of the blends are dependent on the blend composition and the amount of plasticizer present. J. VINYL ADDIT. TECHNOL., 21:102–110, 2015. © 2014 Society of Plastics Engineers